Institutionalization of the national idea in the context of globalization and its socio-philosophical foundations - Umurzakov Uygun Abdutalipovich (Zien Journals, 2022)
This article analyzes the development of Uzbekistan at a new stage of development and its connection with the national idea, the fact that the national idea is an important factor in the development of society.
Keywords: National idea; national idea system; idea; concept